Synthesis and Characterization of Co(II), Ni(II) and Cu(II) Complexes with Some Schiff Bases - RAI, B.K.; THAKUR, R.K.; KUMARI, MINOO; SINGH, J.; BISHEN, R.K. (Asian Journal of Chemistry, 2010)
Metal chelates of Co(ll), Ni(Il) and Cu(II) with Schiff bases have been synthesized by the condensation of 1-oxo-1,2,3,4- tetrahydrocarbazoles with semicarbazide/thiosemicarbazide hydrochloride and characterised by using physico-chemical and spectroscopic methods. The ligands OTCS and OTCTS were suggested to behave as neutral tridentate (N,N,O/S) ligand and have octahedral geometry. The complexes have general composition [M(OTCS)3] and [M(OTCTS)2], M = Co(ll), Ni(lI) and Cu(II). The complexes were found to be non-electrolytic in nature due to low value of electrical conductivity.